2020
DOI: 10.1177/2042098620933741
|View full text |Cite
|
Sign up to set email alerts
|

An overview of prevalence, determinants and health outcomes of polypharmacy

Abstract: A high rate of polypharmacy is, in part, a consequence of the increasing proportion of multimorbidity in the ageing population worldwide. Our understanding of the potential harm of taking multiple medications in an older, multi-morbid population, who are likely to be on a polypharmacy regime, is limited. This is a narrative literature review that aims to appraise and summarise recent studies published about polypharmacy. We searched MEDLINE using the search terms polypharmacy (and its variations, e.g. multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
223
1
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(285 citation statements)
references
References 53 publications
11
223
1
21
Order By: Relevance
“…The prevalence of polypharmacy found in the literature greatly varies. It ranges from around 4% to about 96.5% depending on the age group, definition, healthcare setting and region [7,11]. A cross-sectional analysis [43] from "wave 6" of the Survey of Health, Ageing, and Retirement in Europe (SHARE) database including data from 34,232 participants (mean age: 75.1 ± 7.2 years) revealed that the prevalence of polypharmacy, defined as the concurrent use of five or more medications, in older community-dwelling older adults (aged 65 years or more) ranges from 26.3 to 39.9% across 17 European countries plus Israel [43].…”
Section: Epidemiologymentioning
confidence: 99%
“…The prevalence of polypharmacy found in the literature greatly varies. It ranges from around 4% to about 96.5% depending on the age group, definition, healthcare setting and region [7,11]. A cross-sectional analysis [43] from "wave 6" of the Survey of Health, Ageing, and Retirement in Europe (SHARE) database including data from 34,232 participants (mean age: 75.1 ± 7.2 years) revealed that the prevalence of polypharmacy, defined as the concurrent use of five or more medications, in older community-dwelling older adults (aged 65 years or more) ranges from 26.3 to 39.9% across 17 European countries plus Israel [43].…”
Section: Epidemiologymentioning
confidence: 99%
“…172 Appropriate Polypharmacy' and Medicine Safety During COVID Polypharmacy is one of the most significant prescribing challenges within all health care settings worldwide. 13,184,185 According to WHO: Health care interventions are intended to benefit patients, but they can also cause harm. Every year, a significant number of patients are harmed or die because of unsafe health care, resulting in a high public health burden worldwide.…”
Section: Deprescribing As One Strategy To Reduce Inappropriate Polyphmentioning
confidence: 99%
“…Polypharmacy is a term describing a scenario in which multiple medicines are prescribed to the same patient. Since the term has not been provided with one standard definition, it is most often described as concomitant use of five or more drugs (Masnoon et al, 2017;Khezrian et al, 2020). Of course, polypharmacy is not always a wrong strategy as more complex patients may benefit from what is referred to as 'appropriate polypharmacy' (Hughes, 2020).…”
Section: Introductionmentioning
confidence: 99%